Formação inicial do professor de matemática com uso de tecnologias da informação e comunicação no contexto da escola pública - Souza, Kelen Cristina Pereira de (2016)
This paper intends to analyze which contribution for teachers formative training the participation on extension projects can bring to the bachelors in Mathematics teaching. The research was conducted during the developing of a Project from the Program of Extension - Programa de Extensão UFU/Comunidade (PEIC) in a municipal school located in a country zone from Uberlândia-MG. The research was constituted by a series of activities with students from the ninth year of the Fundamental Education, Middle School. The main focus is the work developed by two bachelors of Mathemactics teaching from the Federal University from Uberlândia who were part of the PEIC team. This present research intends to answer the following question: How the extension project “Information technology and communication on Mathematics problem resolution in country zone schools” has contribited to reinforce and to (re)criate the fomative experiences of students from the Mathematics teaching course who have developed such project? The presente study is from a qualitative nature and has made use of the partaker searching methodology. The presente paper was organized in three chapters. On chapter I evidence is given to theoretical discussion made, having as main references the works of Larrosa, Ponte e Shön. Chapter II brings the description of the three activities that were developed and aplied during the PEIC Project, which are: Problems in the Park, Inaccessible Hight and Lili Game. On chapter III, the data analysis is presented. The data was obtained through instruments of registration such as: camera recording, photografic material, meetings reports, field notes, surveys and semi-structured interviews. The initial hypothesis aim is on the fact that the participation on extention projects during the graduation course can bring rich contribution for the teachers to be, since it’s going to provide the knowledge and chalenge close to the one from the future profession. With the analysis of the obtained results from the colected data, it was possible to conclude that the PEIC has provided the bachelors in Mathematics teching the opportunity of recreate and potenciate their formative experiences. Such opportunity happened in situations that involved, for example, planning makings, development of colective work, softwares usage, different school spaces and the direct interaction with school bureaucracy. Beyond that, it was possible to work with the cocepts of reflection in action in a way to contribute to the professional development of the future Mathematics teachers. Thereby, in our final considerations, is possible to conclude that extension projects performed during the graduation course can bring great contributions to the professional formation of the bachelors in Mathematics teaching, among them we highlight the potentiation of the previous formative experiences and the development of colective work and behavior related to a reflexive teacher.